Does getting away with it count? An application of stafford and warr's reconceptualised model of deterrence to drink driving. (November 2017) - Szogi, E.; Darvell, M.; Freeman, J.; Truelove, V.; Palk, G.; Davey, J.; Armstrong, K.
Highlights: The sample did not believe the likelihood of being apprehended for drink driving was high. A sizable proportion of 311 participants reported drink driving (at least once). Younger males with higher levels of exposure to the road were more likely to drink and drive. Direct punishment avoidance was the most significant predictor of drink driving. No clear links were found between perceptual certainty/severity and self-reported offending behaviours. Abstract: Drink drivers continue to be disproportionately represented in road mortalities and morbidities. Given these costs, countermeasures that effectively reduce the behaviour (and its consequences) are imperative. Research has produced inconsistent findings regarding the deterrent effects of some countermeasures on drink driving behaviour, namely legal sanctions, suggesting other factors may be more influential. This study aimed to determine which deterrence measures based on Classical Deterrence Theory and Stafford and Warr's (1993) reconceptualised model of deterrence influence the propensity to drink and drive over the legal blood alcohol content limit of 0.05. In total, 1257 Australian drivers aged from 16 to 85 years completed a questionnaire assessing their self-reported drink driving behaviour and perceptions of legal sanctions. Consistent with previous research, past experiences of direct punishment avoidance was the most significant predictor of drink driving. Additionally, perceptions of personal certainty of apprehension were a significant (albeit weak) negative predictor of drink driving. Counterintuitively, experiences of indirect punishment were predictive of self-reported drink driving. Similarly, penalty severity produced mixed results as those who considered a penalty would be severe were less likely to drink and drive. However those that considered the penalty would cause a considerable impact on their lives, were more likely to drink and drive. Taken together, these findings suggest that while the threat of apprehension and punishment may influence self-reported drink driving behaviours, committing and offence while avoiding detection is a significant influence upon ongoing offending. This paper will further elaborate on the findings in regards to developing salient and effective deterrents that produce a lasting effect.